The effect of extensive reading on EFL learners writing performance - Yulia Nugrahini; Ika Rakhmawati (JURNAL EDUSCIENCE (JES), 2022)
Extensive Reading (ER) is considered as a good learning technique to enhance every skill in language learning. It is considered to assist the improvement of other skills of  language  learners especially English as a Foreign Language (EFL) leaners. This study is designed to evaluate the effectiveness of ER on EFL learners’ writing performance and to identify the EFL learners’ attitude towards the effects of ER on writing performance. The study recruited a group of 59 non-English majors at a Bhinneka PGRI University. The participants were divided into two groups, i.e., experimental group and control group. The participants in the experimental group were assigned extensive reading materials as  their homework to support their learning of writing meanwhile the participants in the control group were guided to write without the support of extensive reading materials. To check the differences of the participants’ writing ability before and after the intervention, pre-test and post-test were employed. A questionnaire was also delivered to the experimental group after the treatment. The results from the tests revealed that ER supported EFL learners in their writing performance. The experimental group had more significant enhancement. The results obtained from the questionnaire also indicated that  the EFL learners had positive attitudes towards the use of extensive reading materials provided in their writing learning process.